Prognostic Analysis and an Appropriate Antiplatelet Strategy for Patients With Percutaneous Coronary Intervention and High Bleeding Risk: Rationale and Protocol for a Multi-Center Cohort Study - Junyan Zhang; Zhongxiu Chen; Hua Wang; Mian Wang; Chen Li; Sen He; Yong Peng; Jiafu Wei; Yong He (Cardiology Discovery)
Percutaneous coronary intervention (PCI) is an important treatment strategy for patients with coronary artery disease. However, bleeding after PCI significantly increases the mortality risk. The search for prognostic predictors and optimal antiplatelet therapy for patients with high bleeding risk (HBR) after PCI has been a much researched upon topic in current cardiovascular research. However, there is no widely accepted prognostic model or recommended antiplatelet therapy for patients with PCI-HBR. In this trial, based on prospective multi-center database building, we will analyze the adverse prognostic predictors for patients with PCI-HBR, observe the types of antiplatelet drugs and duration of dual antiplatelet therapy in PCI-HBR patients, and compare the safety and feasibility of different antiplatelet regimens and treatment courses. The prognostic analysis and an appropriate antiplatelet strategy for patients with PCI and high bleeding risk (PPP-PCI) trial will help analyze bleeding risk factors in PCI-HBR patients and explore the appropriate antiplatelet treatment options. This study is registered with ClinicalTrials.gov (NCT05369442). The Research Ethics Committee of West China Hospital authorized this study (2022 Review #269). The trial results will be published in peer-reviewed journals and at conferences.